Mapping the Future of Biology Evolving Concepts and Theories - Barberousse, Anouk; Morange, Michel; Pradeu, Thomas (Boston Studies in the Philosophy and History of Science,, 2009)
This volume is the best available tool to compare and appraise the different approaches of today's biology and their conceptual frameworks, serving as a springboard for new research on a clarified conceptual basis. It is expected to constitute a key reference work for biologists and philosophers of biology, as well as for all scientists interested in understanding what is at stake in the present transformations of biological models and theories. The volume is distinguished by including, for the first time, self-reflections and exchanges of views on practice and theoretical attitudes by important participants in recent biological debates. The questions of how biological models and theories are constructed, how concepts are chosen and how different models can be articulated, are asked. Then the book explores some of these convergences between different models or theoretical frameworks. Confronting views on adaptive complexity are investigated, as well as the role of self-organization in evolution; niche construction meets developmental biology; the promises of the emergent field of ecological-evolutionary-development are examined. In sum, this book is a marvellous account of the dynamism of today's theoretical biology.